Human BRCA1 inhibits growth in yeast: Potential use in diagnostic testing - Jeffrey S. Humphrey; Alí Salim; Michael R. Erdos; Francis S. Collins; Lawrence C. Brody; Richard D. Klausner (1997)
Germline-inactivating mutations of BRCA1 result in a hereditary predisposition to breast and ovarian cancer. Truncating mutations of BRCA1 predispose to cancer and can be ascertained by protein truncation testing or sequencing. However, cancer-predisposing missense mutations of BRCA1 are difficult to distinguish from polymorphisms by genetic testing methods currently used. Here we show that expression of BRCA1 or BRCA1 fused to a GAL4 activation domain in Saccharomyces cerevesiae inhibits growth, resulting in small colonies easily distinguishable from vector-transformed controls. The growth inhibitory effect can be localized to sequences encoding the recently described BRCA1 C-terminal domains. Growth suppression by a BRCA1 fusion protein is not influenced by introduction of neutral polymorphisms but is diminished or abolished by frameshift, nonsense, or disease-associated missense mutations located in the C-terminal 305 amino acids of BRCA1. These observations may permit the functional significance of many BRCA1 sequence changes to be assessed in yeast. Additionally, the correlation of growth suppression with wild-type forms of BRCA1 suggests that the assay may be capable of detecting functionally conserved interactions between the evolutionarily conserved BRCA1 C-terminal domains and cellular elements found in both human and yeast cells.